2010
DOI: 10.1093/jxb/erq238
|View full text |Cite
|
Sign up to set email alerts
|

Deviation from the grain protein concentration–grain yield negative relationship is highly correlated to post-anthesis N uptake in winter wheat

Abstract: In plants, carbon and nitrogen (N) economies are intimately linked at the physiological and biochemical level. The strong genetic negative correlation between grain yield and grain protein concentration observed in various cereals is an illustration of this inter-relationship. Studies have shown that deviation from this negative relationship (grain protein deviation or GPD) has a genetic basis, but its physiological basis is still poorly understood. This study analysed data on 27 genotypes grown in multienviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
209
2
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(252 citation statements)
references
References 38 publications
20
209
2
3
Order By: Relevance
“…This is consistent with the study of Bogard et al . (2010), who found that deviations from the grain protein concentration–grain yield relationship in wheat were consistently explained by differences in post‐anthesis N uptake.…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with the study of Bogard et al . (2010), who found that deviations from the grain protein concentration–grain yield relationship in wheat were consistently explained by differences in post‐anthesis N uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Both parameters respond to N fertilization, yet it has been difficult to improve both yield and protein simultaneously. The negative relationship between grain yield and GPC is well established and has a genetic basis (Oury and Godin 2007;Bogard et al 2010;Gaju et al 2011;Oury et al 2003;Barraclough et al 2010;Simmonds 1995). Among 27 wheat genotypes grown in 27 environments ranging in available N (Bogard et al 2010), mean grain yield variability accounted for 78% of mean GPC variability across all environments with a slope of -0.015% g -1 m 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The negative relationship between grain yield and GPC is well established and has a genetic basis (Oury and Godin 2007;Bogard et al 2010;Gaju et al 2011;Oury et al 2003;Barraclough et al 2010;Simmonds 1995). Among 27 wheat genotypes grown in 27 environments ranging in available N (Bogard et al 2010), mean grain yield variability accounted for 78% of mean GPC variability across all environments with a slope of -0.015% g -1 m 2 . The two principle hypotheses to explain the negative correlation of grain yield and GPC are competition for energy resources by C and N assimilation processes (Munier-Jolain and Salon 2005) and a N dilution effect by carbohydrates (Acreche and Slafer 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations